Service Climate and Service Quality of Sri Lankan Public Service: A Partial Least Squares Structural Equation Modeling Approach (PLS-SEM) - Achini Tharanga Wijesekera; R. Lalitha S Fernando (Journal of Business & Management, 2023)
This paper investigates the relationship between service climate and service quality of public service in Sri Lanka. For that, two questionnaires were distributed. The first questionnaire was distributed using random sampling method among 500 employees in 83 Divisional Secretariats to collect data to recognize the level of service climate. The second questionnaire was distributed customers to identify the level of service quality using same sampling method to 2500 customers in the same divisional secretariats. Data were analyzed by SEM using Smart Plus software. The findings revealed that the relationship between service climate (SEC) and perceived service quality (PSQ) is not accepted at 5 percent significance level (P>0.05). It means that the relationship between service climate and perceived service quality is not significant in the context of the Sri Lankan public service. Then it deviates from the previous literature. This empirical finding will help to enhance the body of knowledge in the area of the service quality in the context of the Sri Lankan public service. Similarly this paper filled the important gap in the Sri Lankan literature.